Looking for God: Orthodox Reflections on Bible, Ethics and Liturgy - Plekon, Michael (Cistercian studies quarterly, 2007)
The article reviews the book "Looking for God: Orthodox Reflections on Bible, Ethics and Liturgy," by John Breck.